An integrative approach to the nomenclature and taxonomic status of the genus Blanus Wagler, 1830 (Squamata: Blanidae) from the Iberian Peninsula. Issue 13 (30th March 2018) - Ceríaco, Luis M. P.; Bauer, Aaron M.
ABSTRACT: Presently two species of the genus Blanus are known from the Iberian Peninsula, Blanus cinereus Vandelli, 1797 and Blanus mariae Albert & Fernández, 2009 The latter was recently described based on molecular studies that pointed to the existence of two well-separated lineages on the peninsula. However the description of B. mariae contained several flaws that render the description invalid, namely the designation of an invalid lectotype, the application of the name B. cinereus to a lineage different from that for which it was originally described, and the apparent disregard for the available nomina Amphisbaena reticulata Thunberg, 1787, Amphisbaena rufa Hemprich 1820 and Amphisbaena oxyura Wagler, 1824 Here we use an integrative approach to link morphological, molecular and historical evidence to identify the original type locality of B. cinereus and the population to which the name applies, trace the fate of its type specimen, present a detailed review of the nomenclatural acts and decisions taken by other authors, revise the nomenclatural history of other potentially available nomina, and provide a new nomenclatural arrangement to the group. Blanus mariae is considered a junior synonym of B. cinereus and we describe Blanus vandellii sp. nov. as a new species. A neotype of B. cinereus is also designated and described. www.zoobank.org/urn:lsid:zoobank.org:pub:B3F5DB7E-6F11-49AA-942C-20019E754249